Predictors of Outcome in Inter-hospital Transferred Neurosurgical Patients with Cranial Pathology in a University Hospital in Nepal - Thapa, Bikas; Gurung, Aayushree; Gurung, Ashim; Pradhanang, Amit; Sedain, Gopal; Shilpakar, Sushil Krishna; Sharma, Mohan Raj (Nepal Journal of Neuroscience, 2026)
Introduction: Inter-hospital transfer (IHT) of neurosurgical patients is common; however, little is known about the impact of transfer parameters on clinical outcomes in the South Asian population. Although the transfer process is an important aspect of the continuation of care, the principles of safe transfer are still evolving in low and middle-income countries like Nepal. So, this study aims to describe the current status of IHT in neurosurgical patients and identify the predictors for poor outcomes. Methods: This was a prospective, observational, and analytical study done in the Department of Neurosurgery, Tribhuvan University Teaching Hospital (TUTH). All adult neurosurgical patients with cranial pathology referred from other hospitals were eligible for participation. Patients were admitted and managed as per the departmental protocol. Patients were followed up for 3 months for clinical outcomes, recorded as favorable and unfavorable. Different clinical and transfer parameters were analyzed to identify the predictors of poor outcomes in this patient population. Results: Of 936 neurosurgical patients presenting to TUTH emergency, 337(36.0%) were IHT patients. After the exclusion of 13 patients, 324 patients were included in the final analysis. The median age was 56.9(± 16.1) years. Two hundred ninety (90.0%) patients were transferred in an ambulance with only 2.1% of them being accompanied by a health worker. The overall unfavorable outcome was noted in 134(41.0%) whereas the mortality was 46(14.2 %.) On multivariate regression analysis, low admission Glasgow Coma Scale (GCS) and diagnosis of intracerebral hemorrhage (ICH) were significant predictors of poor outcomes. Conclusion: Inter-hospital transfer is common in neurosurgical practice. Low GCS on admission and diagnosis of ICH were found to be associated with unfavourable outcomes in our study. Though unfavourable outcomes are comparable with those who come directly to the hospital based on the contemporary literature, the practice of safe transfer should be instituted in the country.